ASPEK-ASPEK LINGUISTIK DALAM PROVERBA BAHASA INGGRIS - Iqbal Nurul Azhar (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2014)
This qualitative research is an attempt to explain the structural, lexical, and semantic aspects of English proverbs by using grounded theory approach. The design of this research is embedded single case study which employs Spradley’s qualitative data analysis techniques. This study used non-participant observation method which involved scanning reading and taking-note techniques. The data were then categorized into taxonomies by using distributional and identity method. The result of the research shows that: (1) the structures of English proverbs are varied in forms, from the simple to complex, (2) the inter-constituent relations are not rigid, (3) some unique lexical formulas construct the proverbial structures, and (4) lexicons that construct English proverbs have their own semantic distinctive functions